STRATEGI PENGEMBANGAN OBYEK WISATA DI TAMAN WISATA ALAM TELAGA WARNA - Juanda, Meri; Lidiawati, Ina; Rusli, Abdul Rahman (Universitas Nusa Bangsa, 2021)
TWA Telaga Warna is a Nature Conservation Area which is mainly intended for tourism and nature recreation. TWA Potential of Telaga Warna is not yet known with certainty, given its intangible nature and has recently experienced a decrease in the number of visitors. For this reason, it is necessary to know the potential and strategies for developing tourism objects in TWA Telaga Warna. The method used in this research is based on the analysis of the area of operation of the object of natural tourist attraction (ADO - ODTWA), the index of the feasibility of an object and the analysis of strengths, weaknesses, opportunities and threats (SWOT). Based on the research, it was found that TWA Telaga Warna has potential tourism objects that are worth developing (77.55%) and the TWA Telaga Warna development strategy is the SO strategy, namely maximizing the strength (strength) owned and maximizing the opportunity (opportunity) by preserving the natural good flora. , fauna, natural beauty and water availability of TWA Telaga Warna are the satisfaction of visitors, making infrastructure so that visitors can enjoy natural panoramas and easy access to information, and making tour packages at TWA Telaga Warna in collaboration with the hotel.